Predictive value of selected tests used to assess factors determining sports results of WTF taekwondo athletes - Cieslinski, I.; Gierczuk, D.; Sadowski, J.; Miller, J. (Journal of Combat Sports and Martial Arts, 2015)
Introduction. The aim of the study was to estimate predictive value of selected tests used to assess factors determining very good sports results of taekwondo athletes. Material and methods. The study included 109 taekwondo athletes aged 21.71.78 and it involved measurements of structure, conditioning and flexibility as well as technical, coordination and energetic measurements. An iterative procedure was employed to create a model of logistic regression. Results. In most cases variables describing success factors in sport demonstrated low predictive value regarding the possibilities of predicting success among WTF taekwondo athletes. Of all the examined tests evaluating success factors in taekwondo, the tests that assessed conditioning demonstrated the highest predictive value. Conclusions. Putting an emphasis on factors with the highest predictive value in WTF taekwondo will make it possible to train athletes more economically and to attain sports mastery more quickly.